The Development of Electronic Worksheets Based on SETS (Science, Environment, Technology, and Society) on Virus Topic to Improve Student Critical Thinking Skills - Pramesti, Ertysha Salya; Lisdiana, Lisa (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2024)
The education era challenges institutions to produce generations with 21st-century skills such as critical thinking. SETS learning can enhance these skills by encouraging learners to become active problem solvers. This study aims to produce a SETS-based electronic worksheet to improve critical thinking skills on virus topic that is valid, practical, and effective. This development research uses the ADDIE model. In the study, there were validity, effectiveness, and practicality, as the parameters measured. Quantitative descriptive techniques were used to analyze the data in this research. Based on the scores given by three validators on an electronic worksheet, the average percentage was 3.72 (93.10%) with a very valid category. Based on the assessment of learning outcomes, the post-test achieved a 100% completion score, with an N-gain score of 0.66 placing it in the moderate category. The average completion percentage for each critical thinking indicator was 88.40%, with detail of improvement per indicator of interpretation, analysis, inference, explanation, and self-regulation in order of 40%; 50%; 12%; 22%; and 22%. Based on the responses of 25 students, the average percentage of practicality was 98.88% which was classified as very practical. Based on the three parameters in this study, the SETS-based electronic worksheets are declared feasible to be applied in tenth-grade high school students and can be alternative teaching materials in schools. Students are expected to be motivated to learn, actively participate in the learning process, and have critical thinking skills.